Novel and emerging anesthetic drugs for the treatments of major depression: a comprehensive review of efficacy, mechanism, and outlook - Li, Congyi; Wang, Zhihui; Ye, Xinman; Lv, Jiahui; Chen, Fangming; Zhang, Yining; Liu, Jianhua; Li, Xin; Duan, Jinnian; Wang, Ying; Wang, Bin; Tang, Wei; et al. (Frontiers in Psychiatry, 2025)
Clinical and preclinical studies increasingly support the antidepressant potential of several anesthetic agents, including ketamine, propofol, nitrous oxide (N2O), sevoflurane, and isoflurane. Their therapeutic effects appear to arise from the regulation of multiple interconnected systems: modulation of glutamatergic and GABAergic signaling, interaction with monoaminergic neurotransmitters (5-HT, DA, NE), activation of neuropeptide-related pathways such as BDNF and VGF, regulation of the hypothalamic-pituitary-adrenal (HPA) axis, and suppression of inflammatory responses. These pathways overlap with core pathophysiological changes in depression and thus represent promising targets for intervention. Given the limited efficacy and delayed onset of traditional antidepressants, anesthetics with rapid antidepressant properties have emerged as attractive alternatives. However, their precise mechanisms of action, as well as questions regarding long-term safety and optimal clinical application, remain to be fully clarified. This review summarizes recent advances in both experimental and clinical research on the antidepressant effects of anesthetics, highlighting their underlying molecular and neural mechanisms, therapeutic potential, and current limitations. By integrating mechanistic insights with translational evidence, this article provides new perspectives and serves as a reference for future research aimed at developing safe and effective anesthetic-based therapies for treatment-resistant depression.